A, A Comparison of Vietnamese and French Criminal Laws of Imprisonment - Thị Hồng Hạnh, Nguyễn (VNU Journal of Science: Legal Studies; Vol 33 No 4, 2017)
Abstract: Imprisonment still plays a very important role in the justice systems of each country. Therefore, it is essential for a comparison of Vietnamese and French criminal law to study the provisions of imprisonment. This dissertation explores the factors that affect imprisonment policy, researches legal provisions regarding imprisonment, reviews imprisonment decisions, and provides an overview of the practical execution of imprisonment by Vietnam and the French Republic. On that basis, suggestions are made garnered from the valuable and reasonable experience which the Republic of France has had regarding imprisonment in order to improve criminal law in Vietnam.